(untitled) (UNIZIK Journal of Educational Management and Policy, 2026)
This study investigates artificial intelligence in school security: opportunity and challenges. Drawing insights from a comprehensive review of existing literature and framed within the context of Self-determination Theory (SDT), the research explores the multifaceted contributions of AI across various stages of curriculum development and execution. The study reveals that AI technologies, including machine learning and natural language processing, play a pivotal role in enhancing educational practices. Notably, AI facilitates personalized learning experiences, automates assessments, and optimizes curriculum design by analyzing extensive datasets on student performance. The findings underscore the potential of AI to address scalability issues in education, offering a dynamic approach to curriculum development that considers individual learner needs and ensures the delivery of high-quality educational content. Moreover, the study identifies future prospects for AI in education, envisioning advancements in adaptive learning systems, intelligent tutoring, and expanded applications of AI-driven virtual assistants. Despite the positive impacts, the research acknowledges challenges, such as ethical concerns and the imperative for workforce re-skilling.